Types and Abundance of Periphytonin Glass Substrate in Lake TepianBatuTeratakBuluh Village, SiakHulu District, Kampar Regency, Riau Province - Simangunsong, Perdinan; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT            Periphyton is a microorganism that lives attached to a submerged substrate. This research aims to determine the type and abundance of periphyton in TepianBatu Lake and was conducted in June-July 2019. There are three sampling station, namely S1 (Inlet water channel connecting Lake TepianBatu with Kampar Kanan River), S2 (located floating net cages), S3 (there are water plants and oil palm plantations around the lake). Each station there were2 sampling points, namely the surface (20 cm from the surface of the water) and 2 Secchi (124 cm). The substrate is a glass substrate (8x3 cm2). Substrate placement done 1 week before sampling.Sampling was carried out 3 times with an interval of 1 week. Periphyton samples were collected by spraying glass substrates with distilled water. The periphytonwere preserved with lugol 1% and then identified using an identification book by Prescott (1974), Belcher and Swale (1978), Yunfang (1995), Bigg and Kilroy (2000). Water quality parameters measured were temperature, brightness, pH, dissolved oxygen, free carbondioxide, nitrate and phosphate. Periphyton types found were 24 types consisting of 4 classes, namely Bacillariophyceae class (10 types), Chlorophyceae (9 types), Cyanophyceae (4 types), and Eugelenophyceae (1 type). Total periphyton abundance found during the study ranged from 5022-13176 cells/cm2. The most common type is Melosirasp. Based on the type of periphyton, it was concluded that TepianBatu Lake can be catagorized as eutrophic waters.Keywords: Types, Abundance,Melosirasp, eutrophic